Allergic rhinitis as a systemic disease of respiratory tract - Jasiukiewicz, Eleni; Fabian-Danielewska, Anna; Piątek, Patrycja (Journal of Education, Health and Sport, 2019)
Allergic rhinitis affects nearly 500 million people in the world and is now considered not only to be a local catarrh of the nasal passages, but a chronic systemic respiratory disease. Proof of generalization of this process is the frequent coexistence of asthma and allergic rhinitis. In recognition, the most important role is played by, first of all, a well-collected interview and physical examination. Treatment depends on the form of AR (periodic or chronic) and on the severity of symptoms (mild, moderate or severe). The first-line drugs are nasal glucocorticosteroids and second generation antihistamines. Appropriate treatment allows to reduce ailments and avoid complications, including upper (sinusitis, exudative otitis media, tonsillitis) and lower respiratory tract (bronchial hyperresponsiveness, bronchial asthma), which significantly reduce the quality of life of patients (QOL).